2014
DOI: 10.1021/la501533t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface-Passivating Ligands and Ultrasmall CdSe Nanocrystal Size on the Delocalization of Exciton Confinement

Abstract: Here we report an unprecedentedly large and controllable decrease in the optical band gap (up to 107 nm, 610 meV) of molecule-like ultrasmall CdSe nanocrystals (diameters ranging from 1.6 to 2.0 nm) by passivating their surfaces with conjugated ligands (phenyldithiocarbamates, PDTCs) containing a series of electron-donating and -withdrawing functional groups through a ligand-exchange reaction on dodecylamine (DDA)-coated nanocrystals. This band-edge absorption shift is due to the delocalization of the strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 64 publications
7
58
1
Order By: Relevance
“…37,38 Moreover, the surface ligand interaction has the potential to dramatically alter SCM electronic structure and dictate SCM function more than ligand interactions with larger nanocrystals because smaller SCMs have a greater surface-to-volume ratio that results in a large number of atoms becoming available to interact with the ligands. Our suggestion is supported by dramatic changes in the optical bandgap of (CdSe)34 SCMs upon functionalization of their surface with para-substituted Ph-NH-CS2 -NH4 + and Cd(carboxylate)2 ligands 10,39 as compared to larger CdSe nanocrystals under similar experimental conditions. 7,8,40 Moreover, DFT calculations demonstrate that the (CdSe)34 SCM possesses a stoichiometric (Cd28Se28) composition on its surface.…”
Section: Resultssupporting
confidence: 58%
“…37,38 Moreover, the surface ligand interaction has the potential to dramatically alter SCM electronic structure and dictate SCM function more than ligand interactions with larger nanocrystals because smaller SCMs have a greater surface-to-volume ratio that results in a large number of atoms becoming available to interact with the ligands. Our suggestion is supported by dramatic changes in the optical bandgap of (CdSe)34 SCMs upon functionalization of their surface with para-substituted Ph-NH-CS2 -NH4 + and Cd(carboxylate)2 ligands 10,39 as compared to larger CdSe nanocrystals under similar experimental conditions. 7,8,40 Moreover, DFT calculations demonstrate that the (CdSe)34 SCM possesses a stoichiometric (Cd28Se28) composition on its surface.…”
Section: Resultssupporting
confidence: 58%
“…79 It was previously reported that surface passivating ligands can control exciton delocalization 80 and modulate photophysical properties and such effects are more profound for ultrasmall nanocrystals. 81 The trap state peak position of CdSe(BA/OLA) nanocrystal is red- Figure S9) demonstrated that no residual acetate ions or adsorbed water were present on the nanocrystal surface and it was coated almost exclusively with OLA. Our experimental data are in agreement with the literature that ultrasmall CdSe nanocrystals synthesized in the presence of alkylamines and Cd(acetate)2 produced a stiochiometric core, which is coated with only amines.…”
Section: Fluorescence Lifetime Measurement Of White Light-emitting CDmentioning
confidence: 99%
“…25 Phenyl dithiocarbamate (PDTC, Scheme 1a) ligands have earned lots of attention quite recently, 26,27 because they may greatly influence the electronic and optical features of semiconductor QDs. [28][29][30][31] The absorption spectra of PDTC-capped CdSe QDs display a sizeable redshift with respect to their native counterparts, covered with carboxylate-terminated insulating ligands, e.g. oleic acid.…”
Section: Introductionmentioning
confidence: 99%